#TITLE_ALTERNATIVE# - IRHAM YAMIN (NIM: 15107043) , RASYID
The tide makes sea water level rise and fall periodically in one day. Tidal observations are done to obtain the average water level for a certain period. The data from tidal observations are helpful for vetical datum determination and tide prediction. Apparently, in numbers of tidal observations, there are many cases where some of the tidal data are not recorded. Whereas for the purposes of tidal predictions, the recorded data during the days of measurement need to be completed. Therefore in the study, there will be a series of test which in a one month of tidal observation there is a period when the data are not recorded, and will be filled with artifcial data to enable the process of tidal analysis and tidal predictions for the same month. The tidal analysis generates 29 tidal constituents which will be used for tidal predictions. In this study, from tests of 2 days and 5 days period, the result from the 2-days period is still eligible to be used. The Root Mean Square Error from 2-days period of artificial data is 5 cm and 4 cm for the blank data.